Recent Development and Applications of Polydopamine in Tissue Repair and Regeneration Biomaterials - Guo, Kai; Wang, Yong; Feng, Zi-Xuan; Lin, Xiao-Ying; Wu, Zhang-Rui; Zhong, Xin-Cao; Zhuang, Ze-Ming; Zhang, Tao; Chen, Jian; Tan, Wei-Qiang (International journal of nanomedicine, 2024)
The various tissue damages are a severe problem to human health. The limited human tissue regenerate ability requires suitable biomaterials to help damage tissue repair and regeneration. Therefore, many researchers devoted themselves to exploring biomaterials suitable for tissue repair and regeneration. Polydopamine (PDA) as a natural and multifunctional material which is inspired by mussel has been widely applied in different biomaterials. The excellent properties of PDA, such as strong adhesion, photothermal and high drug-loaded capacity, seem to be born for tissue repair and regeneration. Furthermore, PDA combined with different materials can exert unexpected effects. Thus, to inspire researchers, this review summarizes the recent and representative development of PDA biomaterials in tissue repair and regeneration. This article focuses on why apply PDA in these biomaterials and what PDA can do in different tissue injuries.